A beginner's guide to teaching mathematics in the undergraduate classroom - Kelton, Suzanne (New York : Routledge, 2021)
This practical, engaging book explores the fundamentals of pedagogy and the unique challenges of teaching undergraduate mathematics not commonly addressed in most education literature. Professor and mathematician, Suzanne Kelton offers a straightforward framework for new faculty and graduate students to establish their individual preferences for course policy and content exposition, while alerting them to potential pitfalls. The book discusses the running of day-to-day class meetings and offers specific strategies to improve learning and retention, as well as concrete examples and effective tools for class discussion that draw from a variety of commonly taught undergraduate mathematics courses. Kelton also offers readers a structured approach to evaluating and honing their own teaching skills, as well as utilizing peer and student evaluations. Offering an engaging and clearly written approach designed specifically for mathematicians, A Beginner's Guide to Teaching Mathematics in the Undergraduate Classroom offers an artful introduction to teaching undergraduate mathematics in universities and community colleges. This text will be useful for new instructors, faculty, and graduate teaching assistants alike.
OCLC-licensed vendor bibliographic record.
Keywords: Mathematics -- Study and teaching (Higher); Mathematics; EDUCATION / Teaching Methods & Materials / Mathematics; MATHEMATICS / Study & Teaching; EDUCATION / Higher